2007
DOI: 10.1002/jnr.21257
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein‐expressing cells in the neurogenic regions in normal and injured adult brains

Abstract: In the adult brain, neurogenic stem cells are prevalent in the subventricular zone (SVZ) of the lateral ventricle wall and the subgranular zone (SGZ) in the dentate gyrus. Cells that have structural and molecular characteristics of astrocytes function as neurogenic stem cells in these regions, in which these cells also participate in the creation of the microenvironment that stimulates neurogenesis. In the present paper, we review the phenotypic properties, subpopulations, and proliferation of glial fibrillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
3
13
0
1
Order By: Relevance
“…This antibody stains neural stem cells in the neurogenic regions, the SVZ, and the subgranular zone of the dentate gyrus (Doetsch et al, 1999;Morshead et al, 2003;Zhu and Dahlström, 2007;Ihrie and Alvarez-Buylla, 2008), which is comparable to our results.…”
Section: Antibody Characterizationsupporting
confidence: 93%
“…This antibody stains neural stem cells in the neurogenic regions, the SVZ, and the subgranular zone of the dentate gyrus (Doetsch et al, 1999;Morshead et al, 2003;Zhu and Dahlström, 2007;Ihrie and Alvarez-Buylla, 2008), which is comparable to our results.…”
Section: Antibody Characterizationsupporting
confidence: 93%
“…This was in sharp contrast to our observation in undifferentiated NPCs, where GFAP mRNA levels decreased 100-fold as early as 24 h p.i., with protein declines beginning at 48 h p.i. This suggested that GFAP's function and/or regulation was considerably different in NPCs than in astroglia, which has been suggested by others (80). In our experiments, changes to attachment and spreading characteristics observed during infection of neurospheres paralleled those seen during astroglial differentiation.…”
Section: Discussionsupporting
confidence: 82%
“…To confirm the multipotency of accumulated cells, isolated cells from six mice in the treated and untreated injured groups were pooled, expanded to 70% confluence, and evaluated for their ability to differentiate along ectodermal and mesodermal lineages in vitro. Following culture in conditions of neuroectodermal differentiation, cells from ECM treated mice showed heterogeneous morphologies including spindle-like cells with long processes that expressed β3-tubulin and NeuN, markers of differentiating neurons (26), and stellate shaped cells that expressed glial fibrillary acidic protein (GFAP), a marker of glial cells that is also expressed by some neural stem cells (27,28) (Fig. 3).…”
Section: Ecm Degradation Products Promote the Accumulation Of Mononucmentioning
confidence: 99%